Migraines during pregnancy linked to stroke and vascular diseases: US population based case-control study. (10th March 2009) - Bushnell, Cheryl D; Jamison, Margaret; James, Andra H
Abstract : Objective To examine the association between migraine and cardiovascular diseases during pregnancy. Design US population based case-control study. Setting Nationwide inpatient sample, from the Healthcare Cost and Utilization Project of the Agency for Healthcare Research and Quality. Population 18 345 538 pregnancy related discharges from 2000 to 2003. Main outcome measures Diagnosis of migraine, as identified by ICD-9 codes 346.0 and 346.1. Stroke and other vascular diseases were identified by using standard ICD-9 codes. Results From the hospital discharges with a pregnancy discharge code, 33 956 migraine codes were identified: 185 per 100 000 deliveries. Diagnoses that were jointly associated with migraine codes during pregnancy (excluding pre-eclampsia) were stroke (odds ratio 15.05, 95% confidence interval 8.26 to 27.4), myocardial infarction/heart disease (2.11, 1.76 to 2.54), pulmonary embolus/venous thromboembolism (3.23, 2.06 to 7.07), and hypertension (8.61, 6.43 to 11.54), as well as pre-eclampsia/gestational hypertension (2.29, 2.13 to 2.46), smoking (2.85, 2.53 to 3.21), and diabetes (1.96, 1.64 to 2.35). However, migraine was not associated with several non-vascular diagnoses (pneumonia, transfusions, postpartum infection or haemorrhage). Conclusions In this large, population based sample of pregnant women admitted to hospital, a strong relation existed between active peripartum migraine and vascular diagnoses during pregnancy. Because these data do not allow determination of which came first, migraine or the vascular condition, prospective studies of pregnant women are needed to explore this association further.